-t+1=6t+50

Simple and best practice solution for -t+1=6t+50 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -t+1=6t+50 equation:


t in (-oo:+oo)

1-t = 6*t+50 // - 6*t+50

1-t-(6*t)-50 = 0

1-t-6*t-50 = 0

-7*t-49 = 0 // + 49

-7*t = 49 // : -7

t = 49/(-7)

t = -7

t = -7

See similar equations:

| 7-4n=4n-41 | | 2n-8=5n-2 | | 7a+2=a+2 | | m+10=-20-2m | | -2+7m=-5m+82 | | 2x-6/3=x+7 | | 9-2x=-5x+30 | | -3-6t=7t-16 | | 3+5w=7w-5 | | w+4=7w-26 | | 6n+5=-3n+50 | | 3a-1=2a+2 | | 3m+5=6m-25 | | 9+5=-9+7x | | 4w-5=2w-15 | | 1-6w=4w+71 | | -7-4a=a+13 | | 7w-2=-6w-41 | | 6w+4=w+24 | | m+2=0-m | | h/3=9 | | x(3x+7)=0 | | -6t+2=-6+2t | | -8-2w=-4w+14 | | -2n+4=7n-77 | | -3d-5=-37-7d | | 5t+4=-116-7t | | -5d-1=-4d-7 | | 2b+7=4b+21 | | 7k-4=17+4k | | x-4=6x-34 | | -t+3=t+7 |

Equations solver categories